(untitled) (Bangladesh Journal of Botany, 2022)
Effects of salt stress on seedling growth and ion accumulation in 6 accessions of two Sesbania species viz. S. bispinosa (Jacq.) W. Wight (4 accessions: #1, #5, #7 and #59) and S. cannabina (Retz.) Poir. (2 accessions: #82 and #85), was evaluated in a hydroponic experiment under 0 (control) and 10 dS/m salinity stress. Salt stress significantly affected negatively seedling growth and different ion contents in 6 accessions of Sesbania seedling except for Na+. The relative values, per cent reduction over control, of all morphological and physiological descriptors, were significantly higher indicating superior salt tolerance in accession #59 compared to other accessions studied. The Na+ accumulation was higher in root compared to shoot; however, a reverse scenario was observed for K+ and Ca2+. No distinct difference in salt tolerance was observed between S. bispinosa and S. cannabina. Accession #59 could, therefore, be suggested for cultivation at salineprone areas of Bangladesh. However, it needs further confirmation at the farmer’s saline field condition. Bangladesh J. Bot. 51(1): 157-167, 2022 (March)